(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objectives: The aim of this study was to explore the association of mecA and pvl genes in clinical isolates of MRSA. Materials and Methods: A total of 748 clinical samples were processed by standard microbiological techniques. Colony morphology, Gram’s staining and biochemical tests including catalase, oxidase and biochemical tests were used for the identification. Antimicrobial susceptibility test was performed by Kirby-Bauer disc diffusion technique and their resistance to Methicillin was evaluated using the Cefoxitin disc diffusion method. DNA was extracted by using a modified phenol-based DNA extraction method and finally, the presence of pvl and mecA genes were investigated by the polymerase chain reaction method. Results: Out of 748 clinical samples, (29.4%; 220/748) samples had bacterial growth. Among 220 culture positive isolates, 19.1% (42/220) were positive for S. aureus. Among 42 S. aureus (66.7%; 28/42) were multiple drug resistant (MDR) and 38.1% (16/42) were MRSA. Among 16 MRSA; mecA and pvl genes were positive for 16 (100%) and 7 (43.7%) of the isolates respectively. Seven of mecA positive isolates was positive for pvl gene. Conclusions: It can be concluded from these results that the prevalence of pvl gene is high in MRSA isolates in this study and there is association between the presence of pvl and mecA genes in these isolates.